Real-time detection and portable glucose detection test paper and preparation method thereof
By preparing ZIF-8 crystal film and molecular imprinting technology on filter paper, the problems of complex glucose detection and difficulty in low concentration detection in the prior art are solved, and a portable detection method for real-time rapid visual analysis is realized.
Patent Information
- Application Number
- CN202411183733.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-02-18
AI Technical Summary
The existing glucose detection methods require complex instruments and equipment, are cumbersome to operate, and it is difficult to achieve real-time and rapid visual analysis of low-concentration glucose.
By preparing ZIF-8 crystal film on filter paper, combined with boric acid functionalization and molecular blotting technology, molecular blotting paper base is prepared to achieve real-time rapid visual analysis of low concentration glucose.
Real-time rapid visual analysis of low-concentration glucose is achieved, which is simple and portable to accurately detect glucose in food and biological samples.
Smart Images

Figure CN119470405A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glucose detection, and in particular to a real-time detection and portable glucose detection test strip and a preparation method thereof. Background Art
[0002] Carbohydrates are an important class of organic compounds in nature and are the main source of energy required for all living organisms to maintain life activities. Glucose, as one of the main energy sources for the human body, is often used as a physiological indicator to measure metabolic capacity and monitor the development of diseases. For example, real-time monitoring of glucose concentration in urine sugar and blood sugar is of great significance for controlling the patient's condition. Therefore, the development of glucose sensors has always received widespread attention. In addition, glucose is also a small molecule substance with a relatively abundant content in food. It is often used in food processing. Its content will directly or indirectly affect the quality and shelf life of food. At present, the methods commonly used for glucose detection mainly include high-performance liquid chromatography, spectrophotometry and electrochemical methods. These detection methods have a wide detection range and good specificity, but these methods require the use of instruments and equipment, are complex to operate, and have slow result analysis, which is not conducive to rapid on-site detection. They are also easily affected by changes in instrument parameters and external environment, and have defects such as expensive and time-consuming. In addition, most sugars have similar structures and are mainly distinguished by stereoisomerized hydroxyl functional groups. Therefore, it is difficult to achieve effective separation of sugars.
[0003] Metal organic framework materials (MOFs) have attracted great attention in the fields of catalysis, separation and biochemical sensing due to their high porosity, high specific surface area, adjustable pore size and customizability. However, the binding of MOFs to the target is through ligands and unsaturated metal sites and the target through π-π conjugation, electrostatic adsorption, hydrogen bonding or van der Waals forces. This leads to weak selectivity of MOFs and is easily affected by complex matrices. Molecular imprinting technology (MIT) is a new technology for preparing polymers with specific recognition capabilities for target compounds. Molecular imprinting polymers (MIPs) have the characteristics of high affinity and selectivity, strong resistance to harsh environments, good stability and long service life. They are used in the fields of simulating antibodies and receptors, enzyme simulation catalysis, immunoassay, separation and purification of drugs and herbicides, separation of isomers and enantiomers, selective catalysis, recognition of biomacromolecules such as amino acids and peptides. Therefore, in recent years, many scholars have combined MOFs with molecular imprinting polymers (MIPs) to construct new composite adsorption materials to improve adsorption selectivity. However, there are few reports on the combination of MOFs and molecularly imprinted polymers (MIPs) to construct a colorimetric sensing platform for real-time rapid visual analysis of low-concentration glucose. Summary of the invention
[0004] The purpose of the present invention is to provide a real-time detection, portable glucose test strip and a preparation method thereof. The glucose test strip prepared by the method provided by the present invention can perform real-time rapid visual analysis of low-concentration glucose, and is simple to operate and portable.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a real-time detection and portable glucose test strip, comprising the following steps:
[0007] (1) sequentially performing cleaning pretreatment and poly(p-styrene sulfonate) modification on filter paper to obtain filter paper with negatively charged surface modification;
[0008] The ZIF-8 crystal film is loaded on the surface of the filter paper after the surface negatively charged modification by a secondary growth method to obtain a paper substrate loaded with the ZIF-8 crystal film;
[0009] (2) using tetraethyl silicate and propyltriethoxysilane as raw materials respectively, and sequentially performing surface silanization and surface amination on the paper substrate with the ZIF-8 crystal film loaded on the surface obtained in step (1) to obtain an amination-treated paper substrate;
[0010] (3) immersing the aminated paper base obtained in step (2) into an aqueous solution containing 4-formylphenylboronic acid and sodium cyanoborohydride to carry out a grafting reaction to obtain a boric acid-functionalized paper base;
[0011] (4) immersing the boric acid functionalized paper substrate obtained in step (3) into a PBS buffer solution containing glucose and performing a first oscillation treatment to obtain a paper substrate with a glucose template fixed on the surface;
[0012] The paper substrate with glucose fixed on the surface is immersed in anhydrous ethanol, and then ammonia water and an ethanol solution of tetraethoxysilane are added, and a second oscillation treatment and an elution treatment are performed in sequence to obtain a molecularly imprinted paper substrate;
[0013] (5) Assembling and pasting the cellulose acetate membrane, the molecular imprinting paper-based chip obtained in step (4) and the absorbent pad on the surface of the entire PVC backboard from top to bottom, and then cutting to obtain a real-time detection and portable glucose test strip of a certain size.
[0014] Preferably, the concentration of 4-formylphenylboric acid in the aqueous solution containing 4-formylphenylboric acid and sodium cyanoborohydride in step (3) is 1.5 to 4 mg / mL.
[0015] Preferably, the grafting reaction in step (3) is carried out under light-proof and oscillating conditions, the grafting reaction temperature is 50 to 70° C., and the grafting reaction time is 10 to 14 hours.
[0016] Preferably, the pH value of the PBS buffer solution in the glucose-containing PBS buffer solution in step (4) is 7.5 to 8.5. The concentration of glucose in the glucose-containing PBS buffer solution is 0.5 to 5 mg / mL.
[0017] Preferably, the first oscillation treatment in step (4) is carried out at room temperature, and the time of the first oscillation treatment is 1.5 to 4 hours.
[0018] Preferably, the mass fraction of ammonia in the ammonia water in the step (4) is 1.4 wt %, and the concentration of tetraethoxysilane in the ethanol solution of tetraethoxysilane is 0.5-5 mg / mL.
[0019] Preferably, the second oscillation treatment in step (4) is carried out at room temperature, and the time of the second oscillation treatment is 10 to 60 minutes.
[0020] Preferably, the eluent used for the elution treatment in step (4) is an aqueous solution of acetic acid; and the elution treatment time is 2 to 5 hours.
[0021] Preferably, in step (5), one side of the molecular imprinting paper substrate is in contact with the cellulose acetate membrane, and the other side is in contact with the absorbent pad.
[0022] The present invention also provides a real-time detection and portable glucose test strip prepared according to the method.
[0023] The present invention provides a preparation method of a real-time detection and portable glucose test paper. Two layers of uniform ZIF-8 crystal films are successfully prepared on the surface of filter paper by a secondary growth method, which effectively increases the specific surface area of the filter paper and also provides a pre-enrichment capability for the target analyte. The surface silanization and surface amination modifications provide sufficient conditions for the next grafting reaction. After the grafting of 4-formylphenylboronic acid is completed, in the first oscillation treatment process, the grafted boronic acid group selectively binds to a template molecule glucose with a cis-diol structure under alkaline conditions, thereby achieving the fixation of the template molecule. The free glucose on the surface is removed by elution treatment to obtain a surface fixed test paper. Glucose paper base; subsequently, ammonia water and ethanol solution of the prepolymer solution are used as raw materials for a second oscillation treatment, and an imprinting layer of suitable thickness is formed on the surface of the paper base with glucose fixed on the surface by a sol-gel method. Based on the reversible covalent action mechanism of boron affinity, acetic acid solution can be used to destroy boric acid and elute the template molecule glucose, thereby forming imprinting holes with a size similar to that of the template molecule, and obtaining a molecular imprinting paper base (abbreviated as FZSN-BA@MIP) that can selectively identify and separate glucose molecules. Then, it is assembled with a PVC backing board, a cellulose acetate membrane and a water-absorbent pad to obtain a real-time detection and portable glucose test strip. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The synthetic route of FZSN-BA@MIP and the schematic diagram of target detection in Example 1 of the present invention;
[0025] Figure 2 This is a schematic diagram of the assembly of a portable glucose test strip for real-time detection in Example 1 of the present invention;
[0026] Figure 3 Two configurations of glucose combined with 4-formylphenylboronic acid and their optimized structures in the present invention;
[0027] Figure 4 The color development diagram after adding curcumin-glacial acetic acid solution to different paper-based materials in Example 1 of the present invention, wherein FP is pretreated filter paper, FP@PSS is filter paper with negative surface modification, FZ is paper with ZIF-8 crystal film loaded, FZ@SiO2 is paper with silanized surface, FZS@NH is paper with amino, and FZSN-BA is paper with boric acid functionalization.
[0028] Figure 5 The SEM image of FZ prepared in Example 1 of the present invention, and the XRD images of FP, FZ and ZIF-8 prepared in Example 1, wherein: Figure 5 Figure a is a SEM image. Figure 5 The upper right corner of the middle a is a local magnified 5k times image. Figure 5 b is the XRD pattern;
[0029] Figure 6 The infrared spectra of FZ, FZSN and FZSN-BA prepared in Example 1 of the present invention;
[0030] Figure 7 The X-ray photoelectron spectra of FZ and FZSN-BA@MIP in Example 1 of the present invention, and the energy level peak fitting diagram of N1s and B1s, wherein: Figure 7 a in the figure is FZ, Figure 7 b in the figure is FZSN-BA@MIP. Figure 7 In the figure, c is N1s. Figure 7 The middle d is B1s;
[0031] Figure 8 Thermogravimetric analysis diagrams of FP, FZSN-BA and FZSN-BA@MIP prepared in Example 1 of the present invention;
[0032] Fig. 9 It is a bar graph of the adsorption capacity of FZSN-BA@MIP prepared in Examples 1 to 6 and FZSN-BA@NIP prepared in Comparative Examples 1 to 6 at different imprinting times of the present invention;
[0033] Fig.10 It is the adsorption isotherm model diagram of FZSN-BA@MIP prepared in the embodiment of the present invention and FZSN-BA@NIP prepared in the comparative example, wherein: Fig.10 a and b are the Langmuir models of FZSN-BA@MIP and FZSN-BA@NIP, respectively. Fig.10 c and d are the Freundlich models of FZSN-BA@MIP and FZSN-BA@NIP respectively;
[0034] Fig.11 This is a statistical graph of gray intensity after the FZSN-BA@MIP prepared in Example 1 of the present invention adsorbs and colors different substances under the same conditions;
[0035] Fig.12 This is a diagram showing the color development mechanism of ABTS@GH on glucose in the present invention;
[0036] Fig.13 This is a graph showing the results of glucose testing using the real-time, portable glucose test strip prepared in Example 1 of the present invention, wherein: Fig.13 In the figure, a is a series of glucose colorimetric cards obtained by glucose detection in the application example. Fig.13 b is the standard curve obtained by glucose detection in the application example, and the linear regression equation is y=0.142x+0.588, R 2 =0.9926, Fig.13 Image c in the middle is a glucose low concentration range colorimetric card that was edited after taking a photo with a mobile phone. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing a real-time detection and portable glucose test strip, comprising the following steps:
[0038] (1) sequentially performing cleaning pretreatment and poly(p-styrene sulfonate) modification on filter paper to obtain filter paper with negatively charged surface modification;
[0039] The ZIF-8 crystal film is loaded on the surface of the filter paper after the surface negatively charged modification by a secondary growth method to obtain a paper substrate loaded with the ZIF-8 crystal film;
[0040] (2) using tetraethyl silicate and propyltriethoxysilane as raw materials respectively, and sequentially performing surface silanization and surface amination on the paper substrate with the ZIF-8 crystal film loaded on the surface obtained in step (1) to obtain an amination-treated paper substrate;
[0041] (3) immersing the aminated paper base obtained in step (2) into an aqueous solution containing 4-formylphenylboronic acid and sodium cyanoborohydride to carry out a grafting reaction to obtain a boric acid-functionalized paper base;
[0042] (4) immersing the boric acid functionalized paper substrate obtained in step (3) into a PBS buffer solution containing glucose and performing a first oscillation treatment to obtain a paper substrate with a glucose template fixed on the surface;
[0043] The paper substrate with glucose fixed on the surface is immersed in anhydrous ethanol, and then ammonia water and an ethanol solution of tetraethoxysilane are added, and a second oscillation treatment and an elution treatment are performed in sequence to obtain a molecularly imprinted paper substrate;
[0044] (5) Assembling and pasting the cellulose acetate membrane, the molecular imprinting paper-based chip obtained in step (4) and the absorbent pad on the surface of the entire PVC backboard from top to bottom, and then cutting to obtain a real-time detection and portable glucose test strip of a certain size.
[0045] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0046] The invention sequentially performs cleaning pretreatment and sodium poly(p-styrene sulfonate) modification on the filter paper to obtain the filter paper with negatively charged surface modification.
[0047] In the present invention, the filter paper is preferably Whatman No. 1 qualitative filter paper after cutting. In the present invention, the pretreatment preferably includes: soaking the filter paper in 0.2M hydrochloric acid solution for 20 to 40 minutes, then washing with deionized water for 2 to 4 times, and then vacuum drying at 50°C.
[0048] In the present invention, the poly(p-styrene sulfonate) modification preferably comprises: immersing the pretreated filter paper in a poly(p-styrene sulfonate) solution, and sequentially performing ultrasound, ultrapure water washing and vacuum drying to obtain the filter paper with negatively charged surface modification.
[0049] In the present invention, the mass fraction of sodium polystyrene sulfonate in the sodium polystyrene sulfonate solution is preferably 0.2% to 0.5%; the ultrasonic time is preferably 20 to 40 minutes; the number of ultrapure water rinses is preferably 2 to 5 times; the vacuum drying temperature is preferably 40 to 60 minutes, and the vacuum drying time is preferably 0.5 to 2 hours.
[0050] After obtaining the filter paper with negatively charged surface modification, the present invention adopts a secondary growth method to load the ZIF-8 crystal film on the surface of the filter paper with negatively charged surface modification to obtain a paper base loaded with the ZIF-8 crystal film.
[0051] In the present invention, the method for preparing the paper substrate loaded with ZIF-8 crystal film preferably comprises the following steps:
[0052] (S1) mixing an ultrapure aqueous solution of zinc nitrate hexahydrate and an ultrapure aqueous solution of 2-methylimidazole, stirring at room temperature, centrifuging, washing and drying in sequence to obtain a ZIF-8 seed polymer crystal;
[0053] mixing the ZIF-8 seed polymer crystals and methanol to obtain a ZIF-8 seed suspension;
[0054] The filter paper with negatively charged surface modification is immersed in the ZIF-8 seed suspension, the immersion treatment is repeated twice, and the filter paper is vertically dried to obtain a paper base immersed in the ZIF-8 seed suspension;
[0055] (S2) After mixing zinc nitrate hexahydrate, 2-methylimidazole and ultrapure water, the paper base immersed in the ZIF-8 seed suspension obtained in the step (S1) is placed, and a polymerization reaction is carried out at 28 to 32° C. for 10 to 14 hours, and then the paper base is rinsed with ultrapure water and methanol in sequence, immersed in the methanol solution overnight, and then vacuum dried at 25° C. for 12 hours to obtain a paper base with a ZIF-8 crystal film loaded on the surface.
[0056] In the present invention, the concentration of the ultrapure aqueous solution of zinc nitrate hexahydrate is preferably 20-35 mg / mL, more preferably 23-32 mg / mL, and further preferably 26.6 mg / mL. The concentration of the ultrapure aqueous solution of 2-methylimidazole is preferably 450-600 mg / mL, more preferably 470-550 mg / mL, and further preferably 515.9 mg / mL. In the present invention, the room temperature stirring time is 10-14h; the centrifugal speed is preferably 8000-12000rpm; the centrifugal time is preferably 8-15min. In the present invention, the concentration of ZIF-8 in the ZIF-8 seed suspension is 0.05wt%-0.2wt%; the time of each immersion treatment is preferably 15-25s. In the present invention, the ratio of the mass of zinc nitrate hexahydrate, the mass of 2-methylimidazole and the volume of ultrapure water is (0.06-0.15) g: (1.2-3) g: 40 mL, and more preferably 0.11 g: 2.27 g: 40 mL.
[0057] After obtaining the paper base with the ZIF-8 crystal film loaded on the surface, the present invention uses tetraethyl silicate and propyltriethoxysilane as raw materials respectively, and sequentially performs surface silanization and surface amination on the paper base with the ZIF-8 crystal film loaded on the surface to obtain the amination paper base.
[0058] In the present invention, the surface silanization preferably includes: adding ammonia water to the ethanol solution after heat treatment, ultrasonic mixing, vertically placing the paper base with ZIF-8 crystal film loaded on the surface, adding tetraethyl silicate, and oscillating reaction under light-proof conditions, followed by ultrapure water washing, anhydrous ethanol washing and vacuum drying in sequence to obtain a paper base with silanized surface.
[0059] In the present invention, the temperature of the ethanol solution after heat treatment is preferably 30-45°C; the temperature of the oscillation reaction is preferably 30-45°C, and the time of the oscillation reaction is preferably 6-10 hours; the temperature of the vacuum drying is preferably 40-60°C, and the time of the vacuum drying is 10-14 hours.
[0060] In the present invention, the surface amination preferably comprises: vertically placing a paper substrate with a ZIF-8 crystal film loaded on the surface into an ethanol solution, adding 3-aminopropyltriethoxysilane, performing an oscillating reaction, and then sequentially performing ultrapure water rinsing, anhydrous ethanol rinsing and vacuum drying to obtain a paper substrate with surface amination. In the present invention, the temperature of the oscillating reaction is preferably 50 to 65°C, and the time of the oscillating reaction is preferably 8 to 14 hours; the temperature of the vacuum drying is preferably 30 to 40°C, and the time of the vacuum drying is 0.5 to 2 hours.
[0061] After obtaining the aminated paper base, the present invention immerses the aminated paper base into an aqueous solution containing 4-formylphenylboronic acid and sodium cyanoborohydride to carry out a grafting reaction to obtain a boric acid functionalized paper base.
[0062] In the present invention, the concentration of 4-formylphenylboric acid in the aqueous solution containing 4-formylphenylboric acid and sodium cyanoborohydride is preferably 1.5-4 mg / mL; the concentration of sodium cyanoborohydride in the aqueous solution containing 4-formylphenylboric acid and sodium cyanoborohydride is preferably 1.5-4 mg / mL.
[0063] In the present invention, the grafting reaction is preferably carried out under light-proof and oscillating conditions; the temperature of the grafting reaction is preferably 50-70°C, more preferably 55-65°C; the time of the grafting reaction is preferably 10-14h, more preferably 11-13h. The present invention controls the temperature and time of the grafting reaction within the above range to ensure that the grafting reaction proceeds smoothly, and more boric acid groups are grafted on the surface of the amination-treated paper base, which is beneficial to the subsequent fixation of more template molecules, glucose, and improves the adsorption capacity of the prepared molecularly imprinted paper base for glucose.
[0064] After obtaining the boric acid functionalized paper base, the present invention immerses the boric acid functionalized paper base into a PBS buffer solution containing glucose and performs a first oscillation treatment to obtain a paper base with glucose fixed on the surface.
[0065] In the present invention, the pH value of the PBS buffer solution in the glucose-containing PBS buffer solution is 7.5-8.5; the concentration of glucose in the glucose-containing PBS buffer solution is preferably 0.5-5 mg / mL, more preferably 0.8-3 mg / mL, and further preferably 1 mg / mL; the first oscillation treatment is preferably carried out at room temperature, and the time of the first oscillation treatment is preferably 1.5-4 h.
[0066] After the first oscillation treatment is completed, the present invention preferably rinses the product of the first oscillation treatment with a phosphate buffer solution and naturally dries it to obtain a paper substrate with glucose fixed on the surface.
[0067] After obtaining the paper substrate with glucose fixed on the surface, the present invention immerses the paper substrate with glucose fixed on the surface into anhydrous ethanol, then adds ammonia water and ethanol solution of tetraethoxysilane, and sequentially performs a second oscillation treatment and an elution treatment to obtain a molecularly imprinted paper substrate.
[0068] In the present invention, the mass fraction of ammonia in the ammonia water is preferably 1.4wt%, and the concentration of tetraethoxysilane in the ethanol solution of tetraethoxysilane is preferably 0.5-5mg / mL, more preferably 1-3mg / mL, and further preferably 2.24mg / mL. In the present invention, the second oscillation treatment is preferably carried out at room temperature, and the time of the second oscillation treatment is preferably 10-60min, more preferably 20-40min. In the present invention, the eluent used for the elution treatment is preferably: an aqueous solution of acetic acid with a concentration of 0.1mol / L; the time of the elution treatment is preferably 3-4h.
[0069] After the elution treatment is completed, the present invention preferably rinses the elution product with ultrapure water and anhydrous ethanol in sequence, and then vacuum-dries to obtain a molecularly imprinted paper substrate.
[0070] In the present invention, the number of ultrapure water washing and anhydrous ethanol washing is preferably 2 to 4 times respectively; the temperature of the vacuum drying is preferably 40 to 60° C., and the time of the vacuum drying is 0.5 to 2 hours.
[0071] After obtaining the molecular imprinting paper base, the present invention assembles and adheres the cellulose acetate membrane, the molecular imprinting paper base chip and the absorbent pad on the surface of the entire PVC backboard from top to bottom, and cuts to obtain a real-time detection and portable glucose test strip of a certain size.
[0072] The present invention has no special limitation on the pasting method, and any technical solution known in the art can be used.
[0073] The present invention preferably contacts one side of the molecular imprinting paper substrate with the cellulose acetate membrane and the other side with the absorbent pad. The present invention is assembled in the above manner to provide a strong capillary force and sufficient driving performance for a period of time for the sample to be tested, thereby providing the accuracy of the test results.
[0074] The present invention also provides a real-time detection and portable glucose test strip prepared by the preparation method described in the above technical solution.
[0075] In the present invention, the method for performing glucose detection using the real-time detection and portable glucose detection test strip preferably comprises the following steps:
[0076] Prepare glucose standard solutions with gradient concentrations;
[0077] Insert the absorbent pad ends of several real-time detection and portable glucose test strips into the glucose standard solution respectively for static adsorption. After static adsorption is completed, remove the absorbent pads, rinse the molecular imprinting paper base on the glucose test strips with phosphate buffer, and drip a glucose-specific color developer after surface drying for color development to obtain a series of glucose colorimetric cards;
[0078] Using a mobile phone to photograph the series of glucose colorimetric cards to obtain images of the series of glucose colorimetric cards;
[0079] The grayscale values of the series of glucose colorimetric cards were processed by ImageJ 2X to obtain the grayscale values of the series of glucose colorimetric cards. The concentration of the glucose standard solution was used as the abscissa and the grayscale value of the glucose standard solution after normalization was used as the ordinate to draw a standard curve to obtain a linear regression equation.
[0080] According to the same operation as above, the gray value of the solution to be tested is obtained, and the gray value is substituted into the linear regression equation to obtain the glucose concentration of the solution to be tested.
[0081] In the present invention, the static adsorption time is preferably 10 to 25 minutes. In the present invention, the glucose-specific color developer is preferably obtained by mixing a 20mM ABTS solution, a 10 to 40U / mL GOD solution, and a 20 to 40U / mL HRP solution in a volume ratio of 1:1:1. In the present invention, the glucose-specific color developer is preferably stored at 4°C away from light; the ABTS solution, GOD solution, and HRP solution are preferably prepared using PBS buffer as a solvent.
[0082] The glucose detection test strip provided by the present invention separates sugar compounds based on boron affinity to achieve rapid detection. Glucose in food and biological samples is used as a detection substrate, cellulose filter paper is used as a substrate, a ZIF-8 metal organic framework material is constructed on the filter paper surface by a secondary growth method, and a molecular imprinting paper-based chip is successfully prepared in combination with boron affinity directional surface imprinting technology. Sugar compounds can be separated and enriched based on boron affinity, and glucose in food and biological samples (saliva, serum, urine, etc.) is used as a detection substrate to achieve dual selective adsorption of glucose. This is used as a glucose enrichment and colorimetric sensing platform to assemble a real-time detection and portable glucose detection test strip, which has important reference significance for food field analysis and in vitro diagnosis.
[0083] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0084] Example 1
[0085] A method for preparing a real-time, portable glucose test strip, comprising the following steps:
[0086] (1) Whatman No. 1 qualitative filter paper was cut into equal-sized shapes using a laser engraving machine, soaked in 0.2 M hydrochloric acid solution for 30 min, then rinsed with deionized water three times, and dried in a vacuum drying oven at 50°C to obtain clean filter paper. The clean filter paper was then placed in 20 mL of 0.3% sodium poly(p-styrene sulfonate) (PSS) solution for 30 min of ultrasound, then rinsed with ultrapure water three times, and vacuum dried for 1 h to obtain filter paper with negatively charged surface modification.
[0087] The ZIF-8 crystal film is loaded on the surface of the filter paper after the surface negatively charged modification by a secondary growth method to obtain a paper base loaded with the ZIF-8 crystal film, and the specific steps are as follows:
[0088] (S1) 1.17 g of zinc nitrate hexahydrate and 22.7 g of 2-methylimidazole were accurately weighed into two beakers, and 44 mL of ultrapure water was added to each beaker for ultrasonic dissolution. The two were then mixed and stirred at room temperature for 12 h, and then centrifuged at 10000 rpm for 10 min. The precipitate was collected and washed with ultrapure water and methanol three times respectively. The precipitate was allowed to stand to evaporate the solvent until it was dry, thereby obtaining a white ZIF-8 seed polymer crystal;
[0089] Prepare 20 mL of 0.1% by mass ZIF-8 seed suspension with methanol, immerse the filter paper with negative surface modification in the ZIF-8 seed suspension for 20 seconds, take it out, repeat the immersion treatment twice, then take it out and dry it vertically to obtain a paper base immersed in the ZIF-8 seed suspension;
[0090] (S2) 0.11 g of zinc nitrate hexahydrate and 2.27 g of 2-methylimidazole were weighed and dissolved in 40 mL of ultrapure water, and the paper substrate immersed in the ZIF-8 seed suspension obtained in step (S1) was placed, and the polymerization reaction was carried out in a 30° C. forced drying oven for 12 h. After the reaction was completed, the paper substrate was taken out and rinsed with ultrapure water and methanol for 3 times respectively, and then transferred to 30 mL of methanol solution and soaked overnight. After the soaking was completed, the paper substrate was vacuum dried at 25° C. for 12 h to obtain a paper substrate with a ZIF-8 crystal film loaded on the surface;
[0091] (2) Accurately measure 20 mL of 80% ethanol solution into a screw-capped vial, heat it to 40°C in a water bath, add 500 μL of ammonia solution, and mix it by ultrasonication for 5 min; then vertically place the paper substrate with the surface loaded with ZIF-8 crystal film obtained in step (1) into the screw-capped vial, add 200 μL of tetraethyl silicate, and react at 40°C for 8 h in an oscillation reaction. The reaction process needs to be protected from light throughout; after the reaction is completed, take out the FZ, rinse it with ultrapure water and anhydrous ethanol three times respectively, and dry it in a vacuum at 50°C for 12 h to obtain a surface silanized paper substrate.
[0092] The surface silanized paper substrate was vertically placed in a screw-capped vial containing 20 mL of 50% ethanol solution, 200 μL of 3-aminopropyltriethoxysilane was added and mixed thoroughly, and the mixture was shaken and reacted at 60° C. for 10 h. After the reaction was completed, the mixture was taken out and rinsed with ultrapure water and anhydrous ethanol three times respectively, and dried under vacuum at 35° C. for 1 h to obtain a surface amino-treated paper substrate;
[0093] (3) Prepare the mixture at a concentration of 5 mg / mL -1 10 mL of 4-formylphenylboric acid and sodium cyanoborohydride solution are added, and the two are thoroughly mixed to obtain an aqueous solution containing 4-formylphenylboric acid and sodium cyanoborohydride, and the surface aminated paper base obtained in step (2) is added, and the grafting reaction is carried out at 60° C., in the dark, and under shaking for 12 hours. After the reaction is completed, the paper base is taken out and rinsed with ultrapure water and anhydrous ethanol three times respectively, and dried in vacuum at room temperature for 1 hour to obtain a boric acid functionalized paper base;
[0094] (4) Weighing 0.02 g of glucose after drying and dehydration and dissolving it in 20 mL of PBS buffer solution with a pH value of 8.0, adding the boric acid functionalized paper base obtained in step (3), performing a first oscillation treatment at room temperature for 2 h to fix the template, and rinsing with PBS solution three times after fixation to remove free or loosely bound glucose molecules, and naturally drying to obtain a paper base with glucose fixed on the surface;
[0095] The paper substrate with glucose fixed on the surface was placed in 30 mL of anhydrous ethanol, and 500 μL of ammonia solution and 10 mL of tetraethoxysilane ethanol solution were added, and the second shaking treatment was carried out at room temperature for 30 min. After the treatment, the paper substrate was taken out and rinsed with ultrapure water and anhydrous ethanol three times respectively, and dried under vacuum at 40 ° C for 1 h. 0.1 mol L -1 Acetic acid solution, the elution time and frequency were set to once every 1h, and repeated 3 times in total (i.e., elution treatment for 3h). After the elution, it was rinsed with ultrapure water and anhydrous ethanol 3 times, and vacuum dried at 50℃ for 1h to obtain the molecular imprinting paper substrate, i.e., FZSN-BA@MIP.
[0096] (5) assembling and pasting a cellulose acetate film (180×30 mm), a molecular imprinting paper chip (5×6 mm) obtained in step (4) and a water-absorbing pad on the surface of the entire PVC backboard from top to bottom, and cutting to obtain a real-time detection and portable glucose test strip with a length and width of 30×6 mm;
[0097] One side of the molecular imprinting paper substrate was in contact with the cellulose acetate membrane, and the other side was slightly in contact with the absorbent pad.
[0098] Figure 1 The synthetic route of FZSN-BA@MIP and the schematic diagram of target detection in Example 1 of the present invention; Figure 2 This is a schematic diagram of the assembly of the real-time detection and portable glucose test strip in Example 1 of the present invention.
[0099] Embodiments 2 to 6
[0100] The molecularly imprinted paper-based FZSN-BA@MIP was prepared according to the method of Example 1, except that the time of the second oscillation treatment (also referred to as the imprinting time) in Examples 2 to 6 was 10 min, 20 min, 40 min, 50 min, and 60 min, respectively.
[0101] Comparative Example 1
[0102] The non-imprinted paper-based chip FZSN-BA@NIP was prepared according to the method of Example 1, except that no template molecule glucose was added.
[0103] Comparative Examples 2 to 6
[0104] The non-imprinted paper-based chip FZSN-BA@NIP was prepared according to the method of Example 1. The difference from Example 1 is that no template molecule glucose was added, and the time of the second oscillation treatment (also called imprinting time) in Comparative Examples 2 to 6 was 10 min, 20 min, 40 min, 50 min, and 60 min, respectively. I. Adsorption and recognition mechanism of FZSN-BA@MIP
[0105] The present invention is based on density functional theory (DFT), uses Gaussian 09 software package to optimize the geometric structure of single molecules and molecules after binding, calculates the binding mode and binding energy between the boronic acid ligand (4-formylphenylboronic acid) and the cis-dihydroxyl group of glucose, uses solvent model density (SMD), takes water as a solvent to simulate the influence of the solvent, explores the adsorption recognition mechanism, and obtains two configurations of glucose and 4-formylphenylboronic acid binding and their optimized structures as shown in the figure. Figure 3 As shown. Given that the structure of glucose is relatively simple, its cis-dihydroxyl groups are mainly located at the ortho and meta positions. Therefore, the boric acid ligands are calculated to determine the affinity of the hydroxyl sites 1, 2 and 1, 3 in glucose. Figure 3 The stability of the five-membered cyclic ester and the six-membered cyclic ester formed in a). Figure 3 As shown in b and c, according to the calculation results, [C 13 H 15 BO7] — -1, 2 formed a five-membered cyclic ester binding energy ΔG = -0.617eV, compared to [C 13 H 15 The six-membered ring ester formed by BO7]--2 and 3 has lower binding energy and more stable configuration. The above results show that in the process of glucose adsorption by FZSN-BA@MIP, based on the boron affinity principle, it preferentially combines with its ortho-cis dihydroxyl group to obtain a five-membered ring ester with a more stable configuration.
[0106] 2. Characterization Analysis
[0107] (1) Boric acid verification
[0108] The success of the boronic acid group grafting is directly related to the subsequent directional surface imprinting experimental operation. Therefore, it is necessary to verify the boronic acid grafting of the paper-based material after boronic acid functionalization by a simple and fast method. Referring to the curcumin colorimetric method in the national standard KJ201909, based on the principle that curcumin can react with boric acid in an acidic medium to generate a red product, a curcumin-glacial acetic acid solution was added to the different paper-based materials in Example 1 for color development. The color development diagram of the different paper-based materials in Example 1 after adding the curcumin-glacial acetic acid solution is as follows: Figure 4As shown, FP is the pretreated filter paper, FP@PSS is the filter paper with negative surface charge modification, FZ is the paper substrate loaded with ZIF-8 crystal film, FZ@SiOz is the paper substrate with silanized surface, FZS@NH is the paper substrate with amino modification, and FZSN-BA is the paper substrate with boric acid functionalization. Figure 4 It can be seen that only the surface of the paper-based material FZSN-BA functionalized with boric acid showed a red reaction, indicating that the boric acid grafting was successful.
[0109] (2) SEM and XRD characterization
[0110] The morphological characteristics and elemental analysis of the surface of part of the paper base prepared in Example 1 were carried out by SEM and XRD, and the SEM image of FZ prepared in Example 1 and the XRD images of FP, FZ and ZIF-8 prepared in Example 1 were obtained as shown in FIG. Figure 5 As shown. Figure 5 It can be seen that after magnification of 5k times, the ZIF-8 crystal particles on the FZ surface have dodecahedral characteristics, and the average size of the ZIF-8 crystal particles attached to the paper-based fibers is 1μm±0.2μm. According to the XRD spectrum ( Figure 5 The results presented in (b) show that the spectrum curve of FZ has similar standard characteristic peaks (001), (002) and (112) as the spectrum curve of pure ZIF-8 crystals, further indicating that Example 1 successfully synthesized a ZIF-8 crystal layer on the surface of the FZ paper substrate; wherein FZ and FP have similar broad diffraction peaks at 2θ of 14.8 and 23.4, which is mainly caused by the presence of the filter paper substrate and will not interfere with the analysis of the target peak.
[0111] (3) FTIR characterization
[0112] The infrared spectra of FZ, FZSN and FZSN-BA prepared in Example 1 were obtained by FTIR detection. The results are as follows: Figure 6 As shown by Figure 6 It can be seen that 3332cm -1 The characteristic peaks near the -OH vibration are related to the filter paper substrate. For the spectrum of FZ, 755.78cm -1 The Zn-O stretching vibration peak is at 1145 cm -1 and 1309cm -1 The stretching vibration and tensile vibration of the imidazole ring CN bond are respectively assigned to 1585cm -1 The characteristic peaks near 1650cm are the bending vibrations of the C=N bond. The above characteristic peaks are consistent with those reported in the literature, indicating the successful preparation of ZIF-8 on the paper-based surface. -1 The characteristic peak at 800cm is related to the vibration of the benzene ring. Compared with FZ,-1 and 1100cm -1 New characteristic peaks appeared at 1368 cm-1 in FZSN-BA, belonging to the bending vibration and asymmetric stretching vibration peaks of Si-O-Si, indicating the successful coverage of SiO2 layer. -1 The characteristic peaks near the ZIF-8 surface belong to the BO bond, which further proves that the boronic acid ligand is successfully grafted onto the ZIF-8 surface. It should be noted here that compared with FZ, the characteristic peaks related to ZIF-8 in FZSN and FZSN-BA are not obvious, which may be due to the fact that the coverage of the polymer layer reduces the signal of the characteristic peak of ZIF-8.
[0113] (4) XPS characterization
[0114] XPS was used to analyze the chemical composition and detect the X-ray photoelectron spectra of FZ and FZSN-BA@MIP in Example 1, as well as the energy level peak fitting diagrams of N1s and B1s. Figure 7 In a, two peaks of Zn element in p orbital can be observed, and the corresponding binding energies are 1021.87eV and 1021.32eV, which is consistent with the literature reports. In addition, the binding energies corresponding to the characteristic peaks of O 1s, C 1s, and N1s are 532.74eV, 284.81eV, and 398.96eV, respectively. Figure 7 In a and b, we can observe the extra B1s, Si 2p and Si 2s, and the binding energies corresponding to the three characteristic peaks are 191.16eV, 151.23eV and 102.74eV, respectively. In order to further prove the successful preparation of FZ and FZSN-BA@MIP, the single elements of N1s and B1s were characterized at high magnification. Figure 7 In figure c, two peaks of N1s at 397.8 eV and 401.6 eV can be observed, corresponding to CN and C=N in the ZIF-8 ligand 2-methylimidazole, respectively, proving that ZIF-8 was successfully constructed on the paper-based surface. Figure 7 In the middle d, the B 1s spectrum can be interpreted as two characteristic peaks, of which 190.85 eV corresponds to BO and 191.34 eV corresponds to BC, proving the successful grafting of 4-formylphenylboronic acid on the ZIF-8 surface.
[0115] (5) TG characterization
[0116] The thermogravimetric analysis of FP, FZSN-BA and FZSN-BA@MIP prepared in Example 1 was obtained as shown in Figure 8 As shown, Figure 8The results show that the three materials lose weight for the first time when the temperature is below 300℃. The mass loss of this part may be related to the volatilization of moisture adsorbed by the materials in the environment or residual solvent. When the temperature is greater than 300℃ and gradually increases to 800℃, the three materials all show obvious weight loss, among which the mass loss of FP without any modification is the largest, and the remaining mass percentage is only 5.15%. The mass loss of FZSN-BA mainly comes from the ZIF-8 crystal layer, polymer layer and paper-based material itself on the surface of the paper base. Due to the presence of ZIF-8 crystal layer and some polymer layers, the residual mass of FZSN-BA is more than that of FP without any modification at the same rate temperature. Similarly, FZSN-BA@MIP has an additional SiO2 imprinting layer than FZSN-BA, so the residual mass is a little more than FZSN-BA. In summary, thermogravimetric analysis further proves that ZIF-8 and the imprinting layer are successfully constructed on the surface of the paper base, and have good thermal stability below 300℃, and will not be disturbed by external temperature during daily preparation and analysis.
[0117] 3. Optimization of Blotting Time
[0118] (1) Static adsorption experiment
[0119] The FZSN-BA@MIP prepared under different imprinting time conditions in Examples 1 to 6 and the FZSN-BA@NIP prepared under different imprinting time conditions in Comparative Examples 1 to 6 were treated with a concentration of 20 mg L -1 The glucose solution was subjected to static adsorption, and the residual glucose concentration was detected by ultraviolet spectrophotometer (GB / T 16285-2008) to calculate the adsorption capacity. The imprinting effect was further investigated based on the imprinting factor (IF), and the imprinting factor value was calculated according to formula (1.1):
[0120] IF=Q FZSN-BA@MIP / Q FZSN-BA@NIP (1.1)
[0121] In the formula, the numerator and denominator represent the adsorption capacity of FZSN-BA@MIP and FZSN-BA@NIP for the template molecule glucose, respectively, in mg g -1 .
[0122] Through the above static adsorption, the adsorption capacity of FZSN-BA@MIP prepared in Examples 1 to 6 and FZSN-BA@NIP prepared in Comparative Examples 1 to 6 at different imprinting times was detected. Fig. 9 As shown. Fig. 9It can be seen that when the imprinting time is between 10-30min, the adsorption capacity of FZSN-BA@MIP increases with the extension of imprinting time, while the adsorption capacity of FZSN-BA@NIP decreases with the extension of imprinting time. When the imprinting time is 30min, FZSN-BA@MIP shows the best adsorption performance, and the IF value reaches 3.7. When the imprinting time is greater than 30min, the adsorption capacity of both FZSN-BA@MIP and FZSN-BA@NIP tends to decrease. This may be because the imprinting time is longer, resulting in a thicker imprinting layer, which blocks the holes of the adsorbed template molecules and thus reduces the adsorption capacity of the chip. The adsorption capacity of FZSN-BA@NIP has been decreasing because there are no imprinting holes of suitable template size on its surface, which is non-specific adsorption. The adsorption performance of FZSN-BA@MIP is significantly higher than that of FZSN-BA@NIP, and the adsorption capacity of FZSN-BA@MIP / NIP prepared when the imprinting time is 20-40min is higher, and the highest when the imprinting time is 30min. In the present invention, the imprinting time and the imprinting factor are two key factors for obtaining FZSN-BA@MIP with high recognition performance. The thickness of the imprinted layer and the size of the imprinted cavity can be controlled by controlling the imprinting time.
[0123] (2) Adsorption model analysis
[0124] The above static adsorption results were analyzed using the Langmuir and Freundlich isothermal adsorption models, which are used to describe the chemical adsorption on the adsorbent surface and the single or multilayer adsorption on the heterogeneous surface under non-ideal conditions, respectively. The adsorption isotherm model diagrams of FZSN-BA@MIP prepared in Example and FZSN-BA@NIP prepared in Comparative Example are shown in Figure 2. Fig.10 As shown, Fig.10 a and b are the Langmuir models of FZSN-BA@MIP and FZSN-BA@NIP, respectively. Fig.10 In the figure c and d are the Freundlich models of FZSN-BA@MIP and FZSN-BA@NIP, respectively. The relevant isotherm model fitting parameters are shown in Table 1. The above adsorption model analysis results show that the Langmuir isotherm adsorption model is more suitable for describing the adsorption behavior of FZSN-BA@MIP and FZSN-BA@NIP on glucose, and the determination coefficient R 2 They are 0.996 and 0.993, respectively, which are higher than the R of the Freundlich model. 2 The values belong to the monolayer chemical adsorption under the boron affinity on the adsorbent surface, and the simulated theoretical maximum adsorption capacity is 189.03 mg g -1 and 47.59 mg g -1 , which is close to the experimental value.
[0125] Table 1 Isothermal model fitting parameters of FZSN-BA@MIP prepared in Example and FZSN-BA@NIP prepared in Comparative Example
[0126]
[0127]
[0128] In Table 1, Q m represents the saturated adsorption capacity of FZSN-BA@MIP for glucose at adsorption equilibrium, K L represents the Langmuir adsorption constant, R 2 represents the correlation coefficient, K F represents the Freundlich adsorption constant, and n represents the heterogeneity coefficient.
[0129] 4. Selective Experiments
[0130] In the present invention, FZSN-BA@MIP has a selective adsorption capacity for glucose molecules. Considering the possible impact of various coexisting substances in actual samples on the detection and analysis of target templates, the presence of fructose, sucrose and trace metal elements in the actual honey sample may interfere with the binding between glucose and FZSN-BA@MIP and ultimately affect the detection results. Therefore, some interfering substances were selected for adsorption and color development.
[0131] The specific operation is as follows: 7 pieces of FZSN-BA@MIP prepared in Example 1 were inserted into the -1 The FZSN-BA@MIP was adsorbed in glucose solution, fructose solution, sucrose solution, sodium chloride solution, calcium chloride solution, magnesium chloride solution and potassium chloride solution at room temperature until saturation. After the adsorption, the FZSN-BA@MIP was taken out and rinsed three times with PBS solution to remove free molecules. Then, 4 μL A B T S@GH color developer was added to the dried paper-based interface to observe the color development. The Honor 70 Pro mobile phone was used to take pictures to record the color development results of each FZSN-BA@MIP, and the chip was gray-scaled using ImageJ 2x software.
[0132] The glucose-specific colorimetric agent (abbreviated as ABTS@GH) is obtained by mixing a 20 mM ABTS solution, a 40 U / mL GOD solution, and a 40 U / mL HRP solution in a volume ratio of 1:1:1, and is stored at 4° C. in the dark.
[0133] The gray intensity statistics of the FZSN-BA@MIP prepared in Example 1 after adsorption and coloration of different substances under the same conditions are as follows: Fig.11 As shown. Fig.11It can be seen that after the color developer ABTS@GH was added, only glucose showed a green reaction, and the other substances had no color response, indicating that the presence of coexisting substances in the actual sample would not interfere with the glucose detection results of FZSN-BA@MIP in Example 1, and it has strong specificity and can be used for the analysis and detection of glucose in complex samples.
[0134] 5. Explanation of color development mechanism
[0135] The experiment uses a dual enzyme system + ABTS (ABTS@GOD&HRP, ABTS@GH) as a glucose-specific colorimetric reagent, which can quickly detect glucose colorimetrically at room temperature. Under aerobic conditions, glucose oxidase (GOD) can specifically catalyze the conversion of glucose into gluconolactone and generate an equal amount of hydrogen peroxide. Horseradish peroxidase (HRP) is a heme-containing protein derived from horseradish. Its main function is to use hydrogen peroxide as an electron acceptor to catalyze the oxidation reaction of the substrate to generate ABTS. + The free radical product is green, and thus can be used for visual colorimetric detection of glucose. The color development mechanism of ABTS@GH on glucose in the present invention is shown in the figure. Fig.12 shown.
[0136] 6. Testing of actual samples
[0137] Application Examples
[0138] A method for glucose detection using the real-time detection and portable glucose detection test strip prepared in Example 1, comprising the following steps:
[0139] Prepare a standard glucose solution with gradient concentrations of 0, 0.1 mM, 0.2 mM, 0.4 mM, 0.8 mM, 1.6 mM, and 3.2 mM;
[0140] The absorbent pad ends of the seven real-time detection and portable glucose test strips prepared in Example 1 were respectively inserted into the glucose standard solution and allowed to stand for adsorption for 15 minutes. After the adsorption was completed, the absorbent pads were removed, and the molecular imprinting paper base on the glucose test strips was rinsed with phosphate buffer. After the surface was dried, a glucose-specific color developer was added dropwise for color development to obtain a series of glucose colorimetric cards;
[0141] Using a Honor 70pro mobile phone to shoot the series of glucose colorimetric cards to obtain images of the series of glucose colorimetric cards;
[0142] The grayscale values of the series of glucose colorimetric cards were processed by ImageJ 2X to obtain the grayscale values of the series of glucose colorimetric cards. The concentration of the glucose standard solution was used as the abscissa and the grayscale value of the glucose standard solution after normalization was used as the ordinate to draw a standard curve to obtain a linear regression equation.
[0143] According to the same operation as above, the gray value of the solution to be tested is obtained, and the gray value is substituted into the linear regression equation to obtain the glucose concentration of the solution to be tested.
[0144] The glucose-specific color developing agent is obtained by mixing a 20 mM ABTS solution, a 40 U / mL GOD solution, and a 40 U / mL HRP solution in a volume ratio of 1:1:1, and is stored at 4° C. in the dark.
[0145] The results of glucose detection using the real-time, portable glucose detection test strip prepared in Example 1 are shown in the figure below: Fig.13 As shown, Fig.13 In the figure, a is a series of glucose colorimetric cards obtained by glucose detection in the application example. Fig.13 b is the standard curve obtained by glucose detection in the application example, and the linear regression equation is y=0.142x+0.588, R 2 =0.9926, Fig.13 Image c in the middle is a glucose low concentration range colorimetric card that was edited after taking a photo with a mobile phone.
[0146] As shown in Figure 13, when the glucose concentration is between 0 and 3.2 mM, the green color of the series of glucose colorimetric cards changes in a gradient as the glucose concentration increases. When the concentration is as low as 0.1 mM, the difference between the blank group and the green group can be observed with the naked eye, and the background signal value of the blank group is low, which is conducive to gray value analysis. Fig.13 In a, gray value processing is performed, and the concentration and the corresponding gray value (the gray value is normalized) are plotted and fitted to obtain Fig.13 The standard curve of b, R 2 is 0.9926, indicating that the glucose concentration and the corresponding grayscale value have a good linear relationship. In order to better combine FZSN-BA@MIP with the colorimetric sensing mode and expand its application, a glucose colorimetric card with a concentration range of 0 to 3.2 mM was produced, such as Fig.13 In c, a rapid detection mode integrating enrichment platform and colorimetric sensing was developed and applied to low-concentration glucose detection.
[0147] The detection limit (LOD) and quantification limit (LOQ) of the colorimetric sensor are calculated according to formulas (1.8) and (1.9). In the formula, SD represents the standard deviation of the blank background signal value, and s is the slope of the standard curve.
[0148] LOD=3.3×SD / s (1.8)
[0149] LOQ = 10 × SD / s (1.9)
[0150] After calculation, it is found that the detection limit and quantification limit of glucose colorimetric detection of the real-time detection and portable glucose test strip prepared in Example 1 are 0.02mM and 0.07mM respectively. The detection process does not require the use of complex instruments. The established colorimetric method has the advantages of simple operation and rapid detection. The entire detection process can be completed within 20 minutes.
[0151] (1) Detection of glucose in honey samples
[0152] Two commercially available honeys (both purchased from Yonghui Supermarket) and one kind of farm-collected honey (collected from Lin'an Tianmu Mountain Honey Farmhouse) were selected and numbered 1, 2, and 3 respectively. 1 g (accurate to 0.001 g) of the sample was weighed into a 50 mL volumetric flask, and PBS buffer (0.1 M, pH = 8) was added to dissolve, and the volume was fixed after sufficient shaking. Then, the sample was filtered with filter paper and the initial filtrate was discarded. The filtrate after filtration was filtered through a 0.45 μm microporous filter membrane to obtain three kinds of honey sample solutions, which were stored at 4 ° C for future use.
[0153] Take 1 mL of each of the three honey sample solutions prepared above and dilute them ten times, then use a pipette to take 250 μL of each as the sample to be tested, and use the method of the above application example to detect its gray value, substitute it into the linear regression equation, and obtain the glucose concentration of the solution to be tested. The specific test results are shown in the test paper test values in Table 2.
[0154] The glucose concentrations in the three honey samples were detected by ultraviolet spectrophotometer (GB / T 16285-2008). The results are shown in the UV-Vis detection values in Table 2.
[0155] Table 2 Glucose detection results in honey samples (n=5)
[0156]
[0157] As can be seen from Table 2, for three different honeys, the deviation rate of the results obtained by the two detection methods is between 8.6% and 13.3%, indicating that the method for glucose detection by the real-time detection and portable glucose detection test strip provided by the present invention can be used for the detection of glucose in food, but there is still room for further reducing the deviation rate.
[0158] (2) Detection of glucose in urine
[0159] In order to expand the application of glucose colorimetric sensors, urine was selected as the actual sample for glucose spike detection. China Traditional Chinese Medicine Journal once reported that the detection of glucose in urine is not necessarily related to diabetes. Sometimes glucose may also be detected in urine after consuming foods with high sugar content in a short period of time. But in general, if glucose is detected in the urine of an adult who has not eaten for 12 hours and the concentration is greater than 0.83mM, it is positive and may be related to diabetes. Therefore, the urine samples in this experiment were taken from the morning urine of healthy adults who had fasted overnight for 12 hours, and an appropriate amount of the middle part was taken in a clean container. Accurately measure three identical samples, and then add glucose standard solutions (0.3mM, 0.5mM, 1mM) to each of them, and stir at 5000r min -1 Centrifuge for 5 minutes to obtain a spiked urine sample. Except for the sample spike, the rest of the experimental operation is the same as the above-mentioned detection steps of glucose in the honey sample. The specific test results are shown in the test paper test values in Table 3.
[0160] The glucose concentration in the above-mentioned spiked urine sample was detected by ultraviolet spectrophotometer (GB / T 16285-2008), and the results are shown in the UV-Vis detection values in Table 3.
[0161] Table 3 Recovery and relative standard deviation of glucose in urine samples (n=5)
[0162]
[0163] As can be seen from Table 3, at different glucose spike concentrations, the average recovery rate is 79.3-91.7%, which is satisfactory and closer to the standard method detection result. This shows that the real-time detection and portable glucose test strip prepared in Example 1 can be expanded to urine glucose monitoring in the field of in vitro diagnosis and has development potential.
[0164] In summary, the present invention successfully prepared the FZSN-BA@MIP microfluidic paper-based chip based on the boron affinity strategy, and it has dual recognition performance for glucose (imprinting factor 3.7); the adsorption of glucose by FZSN-BA@MIP conforms to the Langmuir isotherm adsorption model and the pseudo-second-order kinetic adsorption model, and the theoretical maximum adsorption capacity is 213.40 mg / g; combined with the established color development system, a real-time detection and portable glucose detection test strip for real-time rapid visual analysis of low-concentration glucose was constructed, which showed good linearity with the gray value in the concentration range of 0-3.2 mM, and the correlation coefficient R 2The detection limit and quantification limit are 0.02mM and 0.07mM respectively. The sample enrichment and color development of glucose can be completed within 20min, and it has been well applied in the detection of real samples in the fields of food and health monitoring, with a satisfactory recovery rate. The present invention is the first to use boron affinity strategy combined with paper-based microfluidics to build a colorimetric sensing platform for rapid detection of trace glucose in real samples, providing an experimental reference for the application of paper-based microfluidic chips in on-site rapid detection of glucose.
[0165] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a real-time, portable glucose test strip, characterized in that: The following steps are involved: (1) sequentially performing cleaning pretreatment and poly(p-styrene sulfonate) modification on filter paper to obtain filter paper with negatively charged surface modification; The ZIF-8 crystal film is loaded on the surface of the filter paper after the surface negatively charged modification by a secondary growth method to obtain a paper substrate loaded with the ZIF-8 crystal film; (2) using tetraethyl silicate and propyltriethoxysilane as raw materials respectively, and sequentially performing surface silanization and surface amination on the paper substrate with the ZIF-8 crystal film loaded on the surface obtained in step (1) to obtain an amination-treated paper substrate; (3) immersing the aminated paper base obtained in step (2) into an aqueous solution containing 4-formylphenylboronic acid and sodium cyanoborohydride to carry out a grafting reaction to obtain a boric acid-functionalized paper base; (4) immersing the boric acid functionalized paper substrate obtained in step (3) into a PBS buffer solution containing glucose and performing a first oscillation treatment to obtain a paper substrate with a glucose template fixed on the surface; The paper substrate with glucose fixed on the surface is immersed in anhydrous ethanol, and then ammonia water and an ethanol solution of tetraethoxysilane are added, and a second oscillation treatment and an elution treatment are performed in sequence to obtain a molecularly imprinted paper substrate; (5) Assembling and pasting the cellulose acetate membrane, the molecular imprinting paper-based chip obtained in step (4) and the absorbent pad on the surface of the entire PVC backboard from top to bottom, and then cutting to obtain a real-time detection and portable glucose test strip of a certain size.
2. The preparation method according to claim 1, characterized in that: The concentration of 4-formylphenylboric acid in the aqueous solution containing 4-formylphenylboric acid and sodium cyanoborohydride in step (3) is 1.5-4 mg / mL.
3. The preparation method according to claim 1, characterized in that: The grafting reaction in step (3) is carried out under light-proof and oscillating conditions, the grafting reaction temperature is 50 to 70° C., and the grafting reaction time is 10 to 14 hours.
4. The preparation method according to claim 1, characterized in that: The pH value of the PBS buffer solution containing glucose in step (4) is 7.5 to 8.
5. The concentration of glucose in the PBS buffer solution containing glucose is 0.5 to 5 mg / mL.
5. The preparation method according to claim 1, characterized in that: The first oscillation treatment in step (4) is carried out at room temperature, and the time of the first oscillation treatment is 1.5 to 4 hours.
6. The preparation method according to claim 1, characterized in that: The mass fraction of ammonia in the ammonia water in the step (4) is 1.4 wt %, and the concentration of tetraethoxysilane in the ethanol solution of tetraethoxysilane is 0.5-5.0 mg / mL.
7. The preparation method according to claim 1, characterized in that: The second oscillation treatment in step (4) is carried out at room temperature, and the time of the second oscillation treatment is 10 to 60 minutes.
8. The preparation method according to claim 1, characterized in that: The eluent used for the elution treatment in step (4) is an aqueous solution of acetic acid; the elution treatment time is 2 to 5 hours.
9. The preparation method according to claim 1, characterized in that: In the step (5), one side of the molecular imprinting paper substrate is in contact with the cellulose acetate membrane, and the other side is in contact with the absorbent pad.
10. A real-time, portable glucose test strip prepared by the preparation method according to any one of claims 1 to 9.